Voltammetric Amitriptyline Determination Using a Metal-Free Electrode Based on Phosphorus-Doped Multi-Walled Carbon Nanotubes. Issue 1 (21st January 2022) - Sanguarnsak, Chanakarn; Promsuwan, Kiattisak; Saichanapan, Jenjira; Soleh, Asamee; Saisahas, Kasrin; Phua, Cheng Ho; Limbut, Warakorn
Abstract : A new electrode material of phosphorus-doped multi-walled carbon nanotubes (P-MWCNTs) was developed as an electrochemical sensing element for amitriptyline (AMT). P-MWCNTs were hydrothermally synthesized and drop casted on a glassy carbon electrode (P-MWCNTs/GCE). The P-MWCNTs were morphologically, chemically and structurally characterized. The electrochemical characteristics of the P-MWCNTs/GCE were investigated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and adsorptive stripping voltammetry (AdSV). The P-MWCNTs increased electron transfer at the GCE and the electrochemical conductivity of the electrode. Electrocatalytic activity toward the oxidation of AMT was excellent. In the optimal voltammetric condition, the P-MWCNTs/GCE produced linear ranges of 0.50 to 10 μ g ml −1 and 10 to 40 μ g ml −1 . The limit of detection (LOD) and limit of quantification (LOQ) were 0.15 μ g ml −1 and 0.52 μ g ml −1, respectively. The developed sensor displayed good repeatability, reproducibility and specificity. The sensor successfully quantified AMT in pharmaceutical tablets, giving results consistent with spectrophotometric analysis. The sensor achieved recoveries from 98 ± 2% to 101 ± 5% from spiked urine samples. The proposed sensor could be applied to determine AMT in pharmaceutical and urine samples for forensic toxicology.